Value Capture Instruments as An Infrastructure Project Financing Alternative For Rail-Based Mass Transportation: Qualitative Study from The Government Perspective - Koesalamwardi, Ario Bintang; Rostiyanti, Susy Fatena; Reksapernata, Ravli Thaufiq (Universitas Indonesia, 2020)
Increasing the mobility of the working class in urban areas will increase their productivity, which in turn will increase the economic output of the region. This can be achieved by providing a means of mass transportation infrastructure that is fast, affordable, and efficient i.e. rail-based mass transportation. However, the Ministry of National Development Planning estimated there is an infrastructure-funding gap of 4,321 trillion rupiahs to achieve Indonesia's development targets. Inviting the private sector to participate in infrastructure development investment in Land Value Capture (LVC) scheme becomes one of the solutions that need to be studied further. LVC is considered a promising infrastructure financing scheme for the private sector’s investment. However, one of the challenges faced by the government in the application is to identify feasible instruments to capture the value of the land. This study aims to find LVC instruments that are feasible from the perspective of the Indonesian government agency. In-depth interviews with experts from government agencies were conducted to explore the possibilities of LVC instruments that can be applied in Indonesia for mass transportation infrastructure development in urban areas. The result shows that most of the Key Informants (KIs) agree that density bonuses and joint development instruments are applicable LVC schemes for Indonesia. It can be concluded from the analysis that these instruments are better prepared due to the availability of regulations that are mutually beneficial for both the government and the private sector, and has a simpler bureaucratic process.